TEMPORAL MISMATCHES: UNDERSTANDING TENSE ERRORS IN ALBANIAN L2 ENGLISH LEARNERS - Arta KËPUSKA; Arta TOÇI (Prizren Social Science Journal)
This study explores the challenges Albanian learners in Kosovo face while acquiring the English tense system, focusing specifically on common difficulties with tense usage. The research gathered data from questionnaires and written texts, revealing a high incidence of errors in tenses such as the Past Simple, Present Simple, Present Perfect, Past Perfect, and Future Simple. Incorrect tense constructions emerged as the most frequent issue, with native language interference and rule overgeneralization contributing to the learners’ difficulties. Mistakes were particularly prominent in the Past and Present Simple tenses, suggesting that these areas require targeted attention in language instruction. The study emphasizes the need for more comprehensive research, especially through longitudinal and spoken data analysis, to improve teaching strategies for Albanian ESL learners in addressing tense-related errors.